PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM INDUSTRI FARMASI (Studi Empiris Pada PT Kimia Farma Tbk Periode 2011-2022) - Dwi Saputra, Syahrul; Mardiati, Dijan (Journal of Research and Publication Innovation, 2024)
This study aims to determine the impact of Return on Assets (ROA) and Debt to Equity Ratio (DER) on the price of the pharmaceutical industry stock. (Studi Empiris pada PT Kimia Farma Tbk Periode Tahun 2011-2022). The research methods and data types used in this research are quantitative descriptive and secondary data which are financial statements, while the sample type in this study is financial report as balance sheet and profit loss of PT Kimia Farma Tbk period 2011-2022. The analysis used in this study uses the SPSS V.27 test tool. In this study, the data analysis methods used were descriptive analysis test, classical assumption test, multiple linear regression and hypothesis testing. The results of this study indicate that partially the Return on Assets variable has no significant effect on stock prices with a tcount value of 0.294 < t table 2.262, with a significance value of 0.775 > 0.05. While Debt to Equity Ratio partially has a significant effect on stock prices with a tcount value of 2.619> t table 2.262, with a significance value of 0.028 <0.05. Then simultaneously shows the Return on Assets and Debt to Equity Ratio variables have an effect and are significant to the stock price with a fcount value of 7.952> ftabel 4.26 with a significance value of 0.012 <0.05. And the coefficient of determination is obtained at 54.2%, the remaining 45.8% is influenced by variables outside this research.